Liver X receptor agonist upregulates LPCAT3 in human aortic endothelial cells - Bousquet, Delphine; Nader, Elie; Connes, Philippe; Guillot, Nicolas (Frontiers in Physiology, 2024)
Objective: Endothelial cells (ECs) play an important role in tissue homeostasis. Recently, EC lipid metabolism has emerged as a regulator of EC function. The liver X receptors (LXRs) are involved in the transcriptional regulation of genes involved in lipid metabolism and have been identified as a potential target in cardiovascular disease. We aimed to decipher the role of LXRs in the regulation of lipid metabolism in human aortic endothelial cells. Approach and Results: Lipid composition analysis of endothelial cells treated with the LXR agonist T0901317 revealed that LXR activation increased the proportion of polyunsaturated fatty acids (PUFAs) and decreased the proportion of saturated fatty acids. The LXR agonist decreased the uptake of fatty acids (FAs) by ECs. This effect was abolished by LXRα silencing. LXR activation increased the activity and the expression of lysophosphatidylcholine acyltransferase, LPCAT3, which is involved in the turnover of FAs at the sn-2 position of phospholipids. Transcriptomic analysis also revealed that LXRs increased the expression of key genes involved in the synthesis of PUFAs, including FA desaturase 1 and 2, FA elongase 5 and fatty acid synthase. Subsequently, the LXR agonist increased PUFA synthesis and enhanced arachidonic acid, eicosapentaenoic acid, and docosahexaenoic acid content in the EC phospholipids. Modification of the FA composition of ECs by LXRs led to a decrease of arachidonate and linoleate derived prostaglandins synthesis and release. No change on markers of inflammation induced by plasma from sickle cell patient were observed in presence of LXR agonist. Conclusion: These results identify LXR as a key regulator of lipid metabolism in human aortic endothelial cells and a direct effect of LXR agonist on lysophosphatidylacyl transferase (LPCAT3).